Analysis of Factors Influencing Palm Oil Farmers' Income of Production in the Labuhanbatu Regency - Ibnuh Sukoco; Sya'ad Afifuddin; M. Syafii (PT Mattawang Mediatama Solution, 2024)
The research was conducted to determine the factors that affect the income of oil palm farmers in North Labuhanbatu Regency with production as the intervening variable. The income of oil palm farmers is the dependent variable, while land area, fertilizer costs, labor, and selling prices become independent variables and production as an intervening variable. The population in this study involved the people of North Labuhanbatu Regency consisting of eight sub-districts, with a total population of 20,861 oil palm farmers. The sample in this study amounted to 100 farmers. This type of research used primary and secondary data. The method used in this research was path analysis. It is the development of multiple regression analysis by describing the magnitude of the influence of independent variables on the dependent variable indirectly using IBM SPSS AMOS 22. The results of path analysis show that land area, fertilizer costs, and selling prices have an indirect and significant relationship to farmers' income through production, while indirect labor has no influence on farmers in production.